Contribution of MLH1 constitutional methylation for Lynch syndrome diagnosis in patients with tumor MLH1 downregulation. (17th January 2018) - Pinto, Diana; Pinto, Carla; Guerra, Joana; Pinheiro, Manuela; Santos, Rui; Vedeld, Hege Marie; Yohannes, Zeremariam; Peixoto, Ana; Santos, Catarina; Pinto, Pedro; Lopes, Paula; Lothe, Ragnhild; et al.
Abstract: Constitutional epimutation of the two major mismatch repair genes, MLH1 and MSH2, has been identified as an alternative mechanism that predisposes to the development of Lynch syndrome. In the present work, we aimed to investigate the prevalence of MLH1 constitutional methylation in colorectal cancer (CRC) patients with abnormal expression of the MLH1 protein in their tumors. In a series of 38 patients who met clinical criteria for Lynch syndrome genetic testing, with loss of MLH1 expression in the tumor and with no germline mutations in the MLH1 gene (35/38) or with tumors presenting the BRAF p.Val600Glu mutation (3/38), we screened for constitutional methylation of the MLH1 gene promoter using methylation‐specific multiplex ligation‐dependent probe amplification (MS‐MLPA) in various biological samples. We found four (4/38; 10.5%) patients with constitutional methylation in the MLH1 gene promoter. RNA studies demonstrated decreased MLH1 expression in the cases with constitutional methylation when compared with controls. We could infer the mosaic nature of MLH1 constitutional hypermethylation in tissues originated from different embryonic germ layers, and in one family we could show that it occurred de novo. We conclude that constitutional MLH1 methylation occurs in a significant proportion of patients who have loss of MLH1 protein expression in their tumors and no MLH1 pathogenic germline mutation. Furthermore, we provide evidence that MLH1 constitutional hypermethylation is the molecular mechanism behind about 3% of Lynch syndrome families diagnosed in our institution, especially in patients with early onset or multiple primary tumors without significant family history. Abstract : This work aimed to investigate the prevalence of MLH1 constitutional methylation in colorectal cancer patients with abnormal expression of the MLH1 protein in their tumors and without germline mutations. We provide evidence that MLH1 constitutional hypermethylation is the molecular mechanism behind about 3% of Lynch syndrome families, most likely in patients with early onset or multiple primary tumors without significant family history.